A design and fabrication of a solar agriculture water pumping system - Al-Talib, Ammar Abdulaziz Majeed; Noor Idayu, Mohd Tahir; Ain Atiqa, Mustapha; Amar Ridzuan, Abd Hamid; Sarah ‘Atifah, Saruchi; Ibrahim, Yazan Shebli (ALife Robotics Corporation Ltd., 2024)
This study explores the use of a solar driven water pump. PV technology replaces conventional electricity and diesel pumps by using solar energy to power DC or AC water pumps. The main objective of this study is to design and construct a solar-powered agriculture water pumping system and to evaluate its performance. The solar agriculture water pumping system used in this project consists of a 40-watt monocrystalline solar cell with an efficiency conversion of between 23% – 24%. This can supply power to a 16.8 W DC Flow Submersible Pump. It could lift the water up to 5m and a flow range of 700 Liter/Hour. The system also includes a PWM 30A Solar Charge Controller to regulate the input power to a 12V, 7.2A Sealed Rechargeable Battery. Finally, a 20m long watering kit with nozzles irrigation system is connected to a 12V DC Submersible Pump to water the plants.